Breast Cancer Segmentation Based on GVF Snake - Mahfuzah, Mustafa; Nur Azwa, Omar Rashid; Rosdiyana, Samad; Norizam, Sulaiman (2014)
Breast cancer is a mysterious disease that forms through the formation of cancer in the cells of the breast. It is one of the most dangerous cancer diagnosed in women and may lead to the increasing number of deaths all over the world. In this paper, Gradient Vector Flow (GVF) Snake technique is proposed to detect cancerous cells in breast tissues. Ten images of mammograms were tested by using the GVF Snake technique. The mammography images were pre-processed at first using Gaussian Low Pass Filter to remove the unwanted noise and followed by contrast enhancement. After that, the GVF Snake technique is then used to segment the particular cancerous region in the breast tissue as it is allows for flexible initialization of deformable surface and encourages convergence to boundary concavities. The GVF Snake technique showed positive results in segmenting the cancerous region in breast tissue.